2019
DOI: 10.1155/2019/6430486
|View full text |Cite
|
Sign up to set email alerts
|

Management of Diabetes Mellitus in Patients with Chronic Liver Diseases

Abstract: Diabetes mellitus (DM) is a common chronic disease affecting humans globally. During the last few years, the incidence of diabetes has increased and has received more attention. In addition to growing DM populations, DM complications are involving injuries to more organs, such as the heart and cerebral vessel damage. DM complications can reduce quality of life and shorten life spans and eventually also impede social and economic development. Therefore, effective measures to curb the occurrence and development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 79 publications
1
9
0
2
Order By: Relevance
“…Microvascular diabetes complications were associated with both renal disease and peripheral vascular diseases. This relation can explain the significant association of renal disease and amputations, as also known in the recent literature [26,27].…”
Section: Discussionsupporting
confidence: 57%
“…Microvascular diabetes complications were associated with both renal disease and peripheral vascular diseases. This relation can explain the significant association of renal disease and amputations, as also known in the recent literature [26,27].…”
Section: Discussionsupporting
confidence: 57%
“…These observations are consistent with earlier studies, including a recent study from our laboratory animals which demonstrates that metabolic related syndrome such as obesity causes inflammation in the metabolic tissues, particularly the adipose and hepatic tissues [ 47 , 48 ] and these are well documented pathological features of non-alcoholic fatty liver disease [ 47 , 49 ]. This therefore suggests obesity as a predictor of fatty liver disease, which may become one of the common reasons for liver transplantations by 2030 especially in developed countries [ 49 , 50 ]. Other studies have also reported that obestatin could be protective against oxidative stress and inflammation [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is an anorexigenic hormone that suppresses appetite and gastrointestinal motility and modulates growth hormone and lipid metabolism [ 23 , 24 ]. However, previous studies have reported that obestatin acts as antagonist to the actions of ghrelin on appetite, food intake, gastric emptying and the secretion of growth hormone [ 25 , 26 ]. Zhao et al ., also reported that obestatin is reduced in obese humans [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sie sind mit dem Diabetes ätiopathogenetisch und therapeutisch verknüpft. Dazu gehören vordergründig die traditionellen mikro- (Retinopathie, Nephropathie, Neuropathie) und makrovaskulären (koronare Herzerkrankung, periphere arterielle Verschlusskrankheit, Schlaganfall) Diabetesfolgekrankheiten [ 11 , 61 ], aber auch andere ( nichttraditionelle ) ätiopathogenetisch assoziierte Komorbiditäten wie die nichtalkoholische Fettlebererkrankung (NAFLD) mit ihren Komplikationen bis hin zum hepatozellulären Karzinom (HCC: [ 85 , 89 ]), die akute und chronische Pankreatitis [ 18 , 57 , 90 ], das duktale Adenokarzinom des Pankreas [ 12 ] und weitere Krebserkrankungen mit metabolischen Verknüpfungen zum Diabetes [ 69 , 75 ]. Die Erkenntnisse zum (bidirektionalen) Zusammenhang dieser konkordanten Komorbiditäten mit dem Diabetes und den sich daraus ergebenden diagnostisch-therapeutischen Konsequenzen sind teilweise relativ neu und noch nicht flächendeckend von Ärzten aller Fachrichtungen realisiert.…”
Section: Komorbiditäten Bei Diabetes Mellitusunclassified